Pelindian Neodymium dari Magnetik Coal Fly Ash menggunakan Asam Asetat sebagai Pelarut - haries handoyo; I Made Bendiyasa; Agus Prasetya (Eksergi, 2019)
Neodymium (Nd) has been known as a vital component in the modern industry such as for very strong permanent magnets (NdFeB magnet). Some countries are starting to look for alternative sources of Nd such as coal fly ash (CFA), which is the waste from coal combustion. This study aims to look at the potential for Nd extraction from CFA using acetic acid at atmospheric pressure. The effect of CH3COOH concentrations (0,1-1,0 N), and leaching temperature (26-60 oC) was investigated. The experiment was carried out under a constant agitation speed (400 rpm), S/L ratio (3,75 % (W/V)) and CFA particle size (-400 mesh). The highest leaching eficiencies (72%) were achieved for concentration of acetic acid 0,5 N at 60 oC. The leaching kinetics results showed that it best fits the shrinking core model: [t.kap=1-3(1-XB) 2/3 +2(1-XB)] ensuring the overall leaching process is controlled by difussion ash layer. The activation energy determined from the experimental study was of 15,38 kJ/mol.